Solid‐phase micro extraction of food irradiation marker 2‐dodecylcyclobutanone (2‐DCB) from chicken jerky treated with glycerol. Issue 8 (7th July 2020) - Taghvaei, Mostafa; Sommers, Christopher; Ceric, Olgica; Hussain, Faris; Yucel, Umut; Smith, J. Scott
Abstract: The food irradiation marker, 2‐dodecylcyclobutanone (2‐DCB), assayed by SPME provides a fast and simple method to estimate the irradiation history of fat‐containing food products. The SPME conditions were optimized to maximize the extraction of 2‐DCB from chicken jerky treats (CJT) irradiated at low (5 kGy) and high (50 kGy) doses. The extracted 2‐DCB was measured using GC‐MS in selected ion mode ( m/z 98, and 112). Water dilution (1:5) was needed to mobilize 2‐DCB and allow partition to the headspace form the CJT matrix. Increasing the incubation temperature to 80 °C resulted in higher response. Spiking control jerky samples with 2‐DCB from 10 to 150 ng/g CJT compared with spiking water revealed a significant food matrix effect. This method provides a fast, simple, and environmental friendly alternative for the existing solvent extraction methods.